Pengaruh Digitalisasi Layanan Terhadap Profitabilitas Pada Pt. Pos Indonesia Persero, Tbk Periode 2019-2023 - Lanang Maulana; Novia Sandra Dewi; Arlistia Mutmainnah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The shift in consumer habits from conventional to digital requires business actors to adapt to these changes, thus encouraging service providers to transform into digital services in order to adjust to customer interests and also for wider reach. This study aims to analyze the impact of service digitalization on the profitability of PT Pos Indonesia Persero, Tbk during the 2019-2023 period. The analysis technique used in this study is regression analysis. Regression analysis will be used to test the relationship between the independent variable (service digitalization) and the dependent variable (profitability). This study concludes that service digitalization has a positive and significant impact on increasing company profitability. By showing a significant level that shows >5%, so it has a significant effect. Further in-depth research is needed regarding various other aspects that are also influenced by digitalization not only in terms of profitability, but in operations, marketing and other parts.